Transvesical Retzius-Sparing Versus Standard Robot-Assisted Radical Prostatectomy: A Retrospective Propensity Score-Adjusted Analysis - Deng, Wen; Jiang, Hao; Liu, Xiaoqiang; Chen, Luyao; Liu, Weipeng; Zhang, Cheng; Zhou, Xiaochen; Fu, Bin; Wang, Gongxian (Frontiers in Oncology, 2021)
Objectives: To estimate the safety and efficiency of transvesical Retzius-sparing robot-assisted radical prostatectomy (T-RARP) compared with standard robot-assisted radical prostatectomy (S-RARP) for localized prostate cancer (PCa). Materials and Methods: 174 patients bearing localized PCa and undergoing T-RARP or S-RARP between October 2017 and January 2020 were retrospectively enrolled in our analysis. All potential baseline confounders were strictly restrained with propensity-score matching (PM) method (1: 1). Within the matched setting, the perioperative and functional outcomes were compared between the T-RARP and S-RARP groups, while the oncological results and functional recovery of the two arms were presented with Kaplan-Meier curves. Results: Finally, 114 and 60 eligible patients harbouring localized PCa were identified in the S-RARP and T-RARP group, respectively. No significant differences between the two groups were found in all baseline characteristics after PM. Within the matched cohort, no case was converted to open surgery in either group. The T-RARP group was significantly related to a higher mean operative time (p = 0.001) and shorter median hospital stay length (p < 0.001). There were not significant differences in the median estimated blood loss and specimen Gleason score between the two arms. The proportions of transfusion, pT3a disease, postoperative complication, and positive surgical margin in the T-RARP group were also comparable to that in the S-RARP group. The mean prostate-specific antigen and median erectile functional scores did not differ significantly between the two groups at postoperative 3 months and last follow-up. T-RARP vs. S-RARP had significantly improved urinary continence (UC) rates at the removal of catheter (p < 0.001) and postoperative 3 months (p < 0.001), but the significant difference between the two groups in UC recovery disappeared at last follow-up (p = 0.119). No significant difference in biochemical recurrence-free survival was observed following the two surgeries (p = 0.727). Conclusions: T-RARP by experienced hands was feasible for selected patients with clinically localized PCa, yielding significantly improved early return to UC and similar erectile functional preservation without compromising oncological control when compared with the standard approach.